Plastic Deformation in Profile-Coated Elliptical KB Mirrors. (3rd September 2012) - Liu, Chian; Conley, R.; Qian, J.; Kewish, C. M.; Liu, W.; Assoufid, L.; Macrander, A. T.; Ice, G. E.; Tischler, J. Z.
Abstract : Profile coating has been successfully applied to produce elliptical Kirkpatrick-Baez (KB) mirrors using both cylindrical and flat Si substrates. Previously, focusing widths of 70 nm with 15-keV monochromatic and 80 nm with white beam were achieved using a flat Si substrate. Now, precision elliptical KB mirrors with sub-nm figure errors are produced with both Au and Pt coatings on flat substrates. Recent studies of bare Si-, Au-, and Pt-coated KB mirrors under prolonged synchrotron X-ray radiation and low-temperature vacuum annealing will be discussed in terms of film stress relaxation and Si plastic deformation.